Pengaruh Literasi Keuangan, Parental Income, Locus of Control dan Social Influence terhadap Perilaku Keuangan pada Generasi Z di Kabupaten Cilacap - Akmal Elmas Alrofi; Erna Handayani; Wida Purwidianti; Restu Frida Utami (FEB Universitas Maritim Semarang, 2026)
This study aims to analyze the influence of financial literacy, parental income, locus of control, and social influence on the financial behavior of Generation Z in Cilacap Regency. A quantitative approach was employed using a survey method involving 180 Generation Z respondents selected through purposive sampling. The research instrument was developed using a Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess validity, reliability, and relationships among variables. The results indicate that financial literacy, parental income, locus of control, and social influence have positive and significant effects on financial behavior. Social influence emerged as the most dominant factor, followed by locus of control, financial literacy, and parental income. These findings confirm that Generation Z’s financial behavior is shaped not only by financial knowledge but also by family economic conditions, individual self-control, and social environmental influences. This study highlights the importance of integrating financial education, character development, and positive social environments to promote more rational and sustainable financial behavior among Generation Z.